Increased mast cell activation in eosinophilic chronic obstructive pulmonary disease. Issue 9 (26th September 2022) - Higham, Andrew; Dungwa, Josiah; Pham, Tuyet‐Hang; McCrae, Christopher; Singh, Dave
Abstract: Objectives: A subset of chronic obstructive pulmonary disease (COPD) patients have increased numbers of airway eosinophils associated with elevated markers of T2 inflammation. This analysis focussed on mast cell counts and mast cell‐related gene expression in COPD patients with higher vs lower eosinophil counts. Methods: We investigated gene expression of tryptase ( TPSAB1 ), carboxypeptidase A3 (CPA3 ), chymase ( CMA1 ) and two mast cell specific gene signatures; a bronchial biopsy signature (MCbb ) and an IgE signature (MCIgE ) using sputum cells and bronchial epithelial brushings. Gene expression analysis was conducted by RNA‐sequencing. We also examined bronchial biopsy mast cell numbers by immunohistochemistry. Results: There was increased expression of TPSAB1, CPA3 and MCbb in eosinophil high than in eosinophil low COPD patients in sputum cells and bronchial epithelial brushings (fold change differences 1.21 and 1.28, respectively, P < 0.01). Mast cell gene expression was associated with markers of T2 and eosinophilic inflammation ( IL13, CLCA1, CST1, CCL26, eosinophil counts in sputum and bronchial mucosa; rho = 0.4–0.8; P < 0.05). There was no difference in MCIgE gene expression between groups. There was no difference in the total number of bronchial biopsy mast cells between groups. Conclusion: These results demonstrate that eosinophilic inflammation is associated with altered mast cell characteristics in COPD patients, implicating mast cells as a component of T2 inflammation present in a subset of COPD patients. Abstract : Our results demonstrate that eosinophilic inflammation is associated with altered mast cell characteristics in chronic obstructive pulmonary disease (COPD) patients, implicating mast cells as a component of T2 inflammation present in a subset of COPD patients.